Pheochromocytoma: A Clinicopathologic Case Series - I Gusti Ayu Sri Mahendra Dewi; Desak Putu Gayatri Saraswati Seputra (National Cancer Center - Dharmais Cancer Hospital, 2020)
Introduction: Pheochromocytoma is a rare neuroendocrine tumor derived from the chromaffin cells of adrenal medulla. The incidence ranges from 0.005% to 0.1% in the general population.Case Presentation: This case series reported 4 patients with pheochromocytoma who were diagnosed at Sanglah General Hospital Denpasar over a period of three years (2017–2019). The age ranged from 15–59 years with the mean age of 41 + 18.9 years. A similar proportion was found for both sexes. Clinical features include lumps, headaches, flank region pain, palpitations and cold sweat. Hypertension was found in 3 cases. Local examination revealed the solid mass in the flank region in all cases; enlarged lymph nodes were found in one case, namely in the paraaortic region. Abdominal MSCT examination findings showed: a solid mass with cystic components in suprarenal; sizes ranging from 1.9 x 2.6 x 2.2 cm to 21.6 x 14.3 x 17.8 cm; bilateral (1 case), unilateral (3 cases); contrast enhancement and hypervascularization, without calcification (4 cases); central necrotic (1 case). All patients underwent radical adrenalectomy. Microscopic features showed the tumor mass which consisted of the proliferation of chromaffin cells forming alveolar (Zellballen) and solid nest patterns separated by capillary blood vessels. The cells were polygonal-shaped with clear cytoplasm, round-shaped nucleus, and moderate pleomorphic. Mitosis was not found. These histomorphologic findings supported the diagnosis of pheochromocytoma.Conclusions: Diagnosis and optimal treatment plans can be established through rapid and precise recognition of pheochromocytoma in order to achieve better outcomes.